Soliton Solutions of Wu-Zhang System by Generalized Kudryashov Method - Tuluce Demiray, Seyma; Bulut, Hasan; Celik, Ercan (Amer Inst Physics, 2018)
In this paper, generalized Kudryashov method (GKM) is used to find some exact solutions of Wu-Zhang system. Firstly, we get dark soliton solutions of this system by using GKM. Then, we plot graphics of some solutions of this system. Also, we remark results that we found by using this method.
7th International Eurasian Conference on Mathematical Sciences and Applications (IECMSA) -- AUG 28-31, 2018 -- Kyiv, UKRAINE
Keywords: Wu-Zhang system; generalized Kudryashov method and dark soliton solution